Heparin interferes with the uptake of liposomes in glioma - Thomas S. van Solinge; Kristina Pagh Friis; Killian O'Brien; Romy L. Verschoor; Jeroen van Aarle; Arnold Koekman; Xandra O. Breakefield; Pieter Vader; Raymond Schiffelers; Marike Broekman (Elsevier, 2023)
In glioblastoma, a malignant primary brain tumor, liposomes have shown promise in pre-clinical and early phase clinical trials as delivery vehicles for therapeutics. However, external factors influencing cellular uptake of liposomes in glioma cells are poorly understood. Heparin and heparin analogues are commonly used in glioma patients to decrease the risk of thrombo-embolic events. Our results show that heparin inhibits pegylated liposome uptake by U87 glioma and GL261 cells in a dose dependent manner in vitro, and that heparin-mediated inhibition of uptake required presence of fetal bovine serum in the media. In a subcutaneous model of glioma, Cy5.5 labeled liposomes could be detected with in vivo imaging after direct intra-tumoral injection. Ex-vivo analysis with flow cytometry showed a decreased uptake of liposomes into tumor cells in mice treated systemically with heparin compared to those treated with vehicle only.